Central airway stabilization for tracheobronchomalacia improves quality of life in patients with COPD - Ernst, Armin; Odell, David D.; Michaud, Gaetane; Majid, Adnan; Herth, Felix; Gangadharan, Sidhu P. (Chest, 2011)
Background - Tracheobronchomalacia (TBM) is characterized by excessive collapsibility of the central airways, typically during expiration. TBM may be present in as many as 50% of patients evaluated for COPD. The impact of central airway stabilization on symptom pattern and quality of life is poorly understood in this patient population. - Methods - Patients with documented COPD were identified from a cohort of 238 patients assessed for TBM at our complex airway referral center. Pulmonary function testing, exercise tolerance, and health-related quality-of-life (HRQOL) measures were assessed at baseline and 2 to 4 weeks following tracheal stent placement/operative tracheobronchoplasty (TBP). Severity of COPD was classified according to the GOLD (Global Initiative for Chronic Obstructive Lung Disease) staging system. - Results - One hundred three patients (48 women) with COPD and moderately severe to severe TBM were identified. Statistically and clinically significant improvements were seen in HRQOL measures, including the transitional dyspnea index (stent, P = .001; TBP, P = .008), the St. George Respiratory Questionnaire (stent, P = .002; TBP, P < .0001), and the Karnofsky performance score (stent, P = .163; TBP, P < .0001). The improvement appeared greatest following TBP and was seen in all GOLD stages. Clinical improvement was also seen in measured FEV1 and exercise capacity as assessed by 6-min walk test. - Conclusions - Central airway stabilization may provide symptomatic benefit for patients with severe COPD and concomitant severe airway malacia. Operative airway stabilization appears to impart the greatest advantage. Long-term follow-up study is needed to fully ascertain the ultimate efficacy of both stenting and surgical airway stabilization in this patient group. - Trial registry - ClinicalTrials.gov; No.: NCT00550602; URL: www.clinicaltrials.gov
Elektronische Reproduktion der Druckausgabe
Gesehen am 02.05.2022